2015
DOI: 10.4103/0970-2113.168134
|View full text |Cite
|
Sign up to set email alerts
|

Increased metabolic activity of neutrophils in patients with chronic obstructive pulmonary disease

Abstract: Aims:To compare the metabolic activity of peripheral neutrophils in patients diagnosed with chronic obstructive pulmonary disease (COPD) with that of healthy, nonsmoking volunteers.Materials and Methods:Venous blood samples were taken from patients diagnosed with COPD as well as from healthy nonsmokers. Each sample was subjected to the nitro blue tetrazolium (NBT) test in which neutrophils exhibiting elevated metabolic activity were detected by light microscopy. The test was repeated after stimulation with Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Vaidyanathan and Damodar have recently reported that there is an increase in metabolic activity of neutrophils in COPD, which possibly contributes toward lung tissue damage in chronic obstructive pulmonary disease (COPD) subjects. [ 1 ] This letter involves a critical analysis of the observations made by Vaidyanathan and Damodar.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Vaidyanathan and Damodar have recently reported that there is an increase in metabolic activity of neutrophils in COPD, which possibly contributes toward lung tissue damage in chronic obstructive pulmonary disease (COPD) subjects. [ 1 ] This letter involves a critical analysis of the observations made by Vaidyanathan and Damodar.…”
mentioning
confidence: 99%
“…However, I would like to draw the attention toward the most recent published research by Shanmugam et al .,[ 2 ] who happen to report similar findings as that of Vaidyanathan and Damodar. [ 1 ]…”
mentioning
confidence: 99%
See 3 more Smart Citations